The Etiology of Risk in Sexual Offenders: A Preliminary Model. (June 2019) - Brouillette-Alarie, Sébastien; Proulx, Jean
Sexual offender risk assessment practice is considered by many to be atheoretical. The identification of the most predictive risk factors and tools has typically overshadowed questions about etiology. To gain insight into the origins of criminal behavior among sexual offenders, we developed and validated an etiological model of risk based on the theoretical framework of Beech and Ward. Our model focused on persistence rather than onset, and encompassed both the sexual and nonsexual criminal activity of these offenders. It comprised two pathways. The first was characterized by sexual victimization, social isolation, and early deviant sexual fantasies. It led to a prolific involvement in sexual criminality (especially toward children) and predicted sexual recidivism. The second pathway was characterized by externalization problems, sexual promiscuity, and physical/psychological victimization, and was associated with nonsexual offending and serious sexual offenses directed (mostly) toward women. It predicted all types of recidivism.